MISOGINISTIK DALAM NASKAH JAWA KUNO - Ruhama wazna; Nurul Khansa Fauziyah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Negative stigmas against women are found in ancient Javanese culture, including in the manuscript of Serat Sandi Wanita. This paper aims to uncover the histories of misogynistic hadith in the manuscript, assess their quality, and examine how the manuscript’s initiators and writers constructed the hadith or history. This paper is a qualitative study with historical and gender analyses, as well as a hadith-critical approach. Furthermore, it was found that there are two narrations in the manuscript that use the figures of the Prophet (peace be upon him) and his family, namely Fatimah r.a. and Ali bin Abi Talib r.a as role models but contain misogynistic values of Hinduism. Theological syncretism between Islam and Hinduism, as a characteristic of Javanese Islam in the 19th century, has influenced the use of hadith histories in Serat Sandi Wanita. These narrations cannot be accepted as arguments because they do not meet the requirements for the validity of the hadith in both sanad and matan. This study emphasizes the importance of reviewing and criticizing hadith in local texts or studies that contain narrations attributed to the Prophet PBUH. This research also contributes to enriching the new direction of hadith and gender studies in Indonesia through an interdisciplinary approach to the authority of Islamic texts within local culture, thereby enabling a deeper identification of the root causes of the construction of hadith-based gender injustice.